Financing the implementation of HR engineering in manufacturing enterprises in the context of the country's digital economy formation - Inga Bumane; Rosita Zvirgzdina; Nadiia Hura; Volodymyr Metelytsia; Iryna Otenko; Mykhailo Bialoshytskyi (Financial and Credit Activity: Problems of Theory and Practice, 2024)
The article is devoted to the study of possible prospects for financing the implementation of HR engineering at manufacturing enterprises in the conditions of the formation of a digital economy. In the process of research, the authors considered the possibilities of implementing HR engineering at production enterprises and focused attention on the main directions of implementation. The principles of financing enterprises that implement changes and transform are revealed. Approaches and strategies aimed at optimizing human capital management in the company are proposed. The authors noted the following main tools of HR engineering for the development and improvement of HR processes, which are key to building effective human capital management strategies in the organization and require funding: organizational management structure, strategic maps, creation of a portrait of personnel competencies, modelling of the human resources management process resources, development of a goal tree, increased flexibility of HR management processes, implementation of a balanced system of indicators. The authors' comprehensive analysis of the implementation of digital HR solutions by manufacturing enterprises in previous years made it possible to identify the most important obstacles to the successful implementation and financing of innovations and digital solutions, the main of which are: insufficient financial resources for the implementation of innovative projects; lack of sufficient financial assistance and stimulation from the state; large financial costs associated with changes in the infrastructure and introduction of new technologies; low interest of investors, which may limit access to external sources of financing; some innovations may require a long payback period, which becomes a challenge for companies; high interest rates on loans can make it difficult to finance innovative projects. Considering these financial factors, it is important to develop comprehensive strategies and tools to overcome obstacles and stimulate the innovative and digital development of manufacturing enterprises. – – HR- . HR- . , . , . HR- HR-, : , , , , , HR-, . HR- , : ; ; , ' ; , ; , ; . , - .
Keywords: L86; 330; digitalization; financing; HR-engineering; industry; innovations; infrastructure; partnership for the goals; HR-